A clinical trial comparing trauma‐informed guilt reduction therapy (TrIGR), a brief intervention for trauma‐related guilt, to supportive care therapy. Issue 4 (25th January 2022) - Norman, Sonya B.; Capone, Christy; Panza, Kaitlyn E.; Haller, Moira; Davis, Brittany C.; Schnurr, Paula P.; Shea, M. Tracie; Browne, Kendall; Norman, Gregory J.; Lang, Ariel J.; Kline, Alexander C.; Golshan, Shahrokh; et al.
Abstract: Introduction: Trauma‐related guilt is common, associated with posttraumatic mental health problems, and can persist after posttraumatic stress disorder (PTSD) treatment. We compared the efficacy of two six‐session psychotherapies, Trauma‐Informed Guilt Reduction (TrIGR) and Supportive Care Therapy (SCT), for reducing trauma‐related guilt. TrIGR helps patients accurately appraise their role in the trauma and re‐engage in values. In SCT, patients guide session content. Methods: A total of 184 veterans seeking VA mental health services were enrolled across two sites; 145 veterans (mean age: 39.2 [8.1]; 92.4% male; 84.8% with PTSD) who endorsed guilt related to a traumatic event that occurred during a post 9/11 Iraq or Afghanistan deployment were randomized and assessed at baseline, posttreatment, 3‐ and 6‐month follow‐up. Results: Linear mixed models using intent‐to‐treat analyses showed guilt decreased in both conditions with a greater decrease for TrIGR (treatment × time, −0.22; F 1, 455.2  = 18.49, p  = .001; d  = 0.92) than supportive therapy. PTSD and depressive symptoms showed the same pattern. TrIGR had significantly higher likelihood of PTSD treatment response (67% vs. 40%), loss of PTSD diagnosis (50% vs. 14%), and meaningful change in depression (54% vs. 27%) than supportive therapy. Psychological distress and trait shame improved in both conditions. Quality of life did not change. Conclusions: Targeting guilt appears to be an effective means for reducing posttraumatic symptoms and distress.